PREPARATION AND CHARACTERIZATION OF THE MONOMETAL CATALYST Mo/ USY - Nugrahaningtyas, Khoirina Dwi; Trisunaryanti, Wega; Triyono, Triyono; Nuryono, Nuryono; Widjonarko, Dian Maruto; Mulyani, Mulyani (Alchemy Jurnal Penelitian Kimia, 2012)
This research deals with preparing and characterizing the metal based-catalyst of Mo supported on Ultra Stable Y-zeolite (USY) and, is aimed to ascertain the best produced catalyst for hydrotreatment reaction in standpoint of its capabilities on removing the unwanted-heteroatom compounds.Procedure of catalyst treatment was preparation, activation and characterization. Monometal catalyst Mo/USY was prepared under variation concentrations of salt metal precursor (concentrations), i.e 2, 6, 10 and 14% wt. The activation steps were carried out by calcination, oxidation, and reduction. Characterization of catalysts were determined by data of XRD, AAS, acidity, surface area and its porosity. The result shows that these catalysts have several good characters that supporting their usefulness in hydrotreatment-catalytic reaction. In addition, catalyst Mo10/USY performs many ideal criteria as the best functional catalyst.